Hemorrhagic Pancreatitis in Pediatric Heart Transplant Recipients. (9th November 2022) - Schwietert, M; Sanabria Nunez, D; Petty, D
Abstract: Introduction/Objective: Acute pancreatitis is a known side effect of tacrolimus in solid organ transplant recipients, but can be difficult to detect as symptoms may be vague and poorly localized, or overlap with the underlying condition. This phenomenon has most frequently been described in adult kidney transplant recipients. We present two autopsy cases in which pediatric patients with history of orthotopic heart transplantation both developed hemorrhagic pancreatitis shortly following operative procedures. Both had received immunosuppressants including tacrolimus during therapy. Although the etiology of pancreatitis in these medically complex cases is likely multifactorial, tacrolimus may be an important contributor. Methods/Case Report: Case 1: A 6-year-old male with hypoplastic left heart syndrome was admitted for two years for medical management while awaiting transplant. Prior to and following transplantation he received immunosuppressants including tacrolimus to reduce risk of transplant rejection. Two weeks post-operatively, he developed abdominal pain and elevated pancreatic enzymes, leading to a diagnosis of pancreatitis. Imaging revealed hemorrhage. Tacrolimus was suspected to have caused this, and was discontinued. Despite medical management and multiple attempts to embolize vessels around the pancreas, the decedent remained unstable and ultimately went into hypotensive bradycardic cardiac arrest. Autopsy revealed a large hemorrhagic cavity confluent with a necrotic pancreas, as well as coagulum adherent to bowel loops throughout the abdomen. Case 2: A 13-year-old male status post two orthotopic heart transplants presented for a dental procedure. Following this, he developed an anaphylactic-type reaction to medication, with hives and bradycardia followed by cardiac arrest. He was resuscitated, however, his cardiac function steadily declined throughout the remainder of his stay. Heart biopsy revealed no evidence of cell-mediated transplant rejection. Pancreatic enzymes were mildly elevated, and abdominal imaging was unremarkable. His tacrolimus levels were noted to be supratherapeutic, and this was discontinued. Shortly before passing, he developed severe abdominal pain with distension, nausea and vomiting. At autopsy, he was found to have nearly two liters of hemorrhage and clot within the peritoneum emanating from a necrotic and hemorrhagic pancreas. Results (if a Case Study enter NA): NA. Conclusion: Close clinical monitoring of pancreatic function should be considered in solid organ transplant recipients receiving tacrolimus.